Analysis of Managerial Support, Communication Patterns, and Work Motivation in Shaping the Quality of Medical Team Performance - Az Zahra Shafira Subhan; Saparuddin Lalu; Mustamin Mustamin (Newinera Publisher, 2026)
The quality of medical team performance constitutes a crucial determinant of excellence in hospital services. Organizational dimensions such as managerial support, communication patterns, and work motivation are widely recognized as key factors influencing employee performance within healthcare institutions. A comprehensive understanding of the relative contributions of these variables is essential for the formulation of effective human resource management strategies. This study aims to examine the influence of managerial support, communication patterns, and work motivation on the quality of medical team performance at Benyamin Guluh Hospital Kolaka. This research employed a quantitative approach utilizing a survey design. Data were collected through structured questionnaires administered to 78 medical personnel. The data were analyzed using Partial Least Squares–Structural Equation Modeling with the assistance of SmartPLS software to assess the relationships among variables and test the proposed hypotheses. The findings reveal that managerial support and communication patterns do not exert a statistically significant effect on the quality of medical team performance. Conversely, work motivation demonstrates a positive and significant influence and emerges as the most dominant factor affecting performance outcomes. The coefficient of determination (R²) value of 0.499 indicates that managerial support, communication patterns, and work motivation collectively account for 49.9% of the variance in medical team performance. Work motivation plays a central role in enhancing the quality of medical team performance. The implementation of targeted motivational strategies among medical personnel proves more effective than relying solely on managerial support or communication enhancement initiatives.